Congenital Complete Atrioventricular Block and Dilated Cardiomyopathy: New Light for an Old Disease. (9th August 2012) - Paiva, Mariana; Ribeiro, Vania; Garcia, Raquel; Amorim, Sandra; Campelo, Manuel; Martins, Elisabete; Moura, Brenda; Cardoso, Jose; Maciel, M. Júlia
Abstract : We present a case of a patient with known complete congenital atrioventricular block (CAVB) since the age of 7 years old that developed dilated cardiomyopathy ten years after VVI-R pacemaker implantation. He presented severe biventricular dysfunction and was symptomatic despite optimal medical therapy. Cardiac resynchronization therapy was used, and he showed clinical and electrocardiographic improvement a month later.